The Dominance of physico-morphic plant traits in regulating population density of Bemisia tabaci and Thrips tabaci in Bt and non-Bt Cotton - Asad Saleem, Muhammad Ishtiaq, Mirza Abdul Qayyum, Muhammad; ullah, Aboubakar Siddique, Ghulam Murtaza, Saif (Journal of Scientific Agriculture, 2019)
Policy makers, journalists and other commentators often advocate transgenic cotton (Gossypium spp.) as poor-performer against sucking insects that pose a great threat to production targets. A field study was carried out for seasonal occurrence of whitefly (Bemisia tabaci Gennadius) and thrips (Thrips tabaci Lindeman) on two of cotton genotypes namely Bt MNH-992 and non-Bt Cyto-124 under climatic conditions of Multan, Pakistan from July-October, 2017. Impact of environment as a factor was hypothesized on pests on two experimental sites [Research Area (RA) & Farmer Field (FF)]. Maximum population of whitefly at RA (13.5 and 16.7 individuals per plant) for Bt and non-Bt, respectively was recorded during SMW 40, while correspondent minimum populations (0.6 & 1.2 individuals per plant) was found during SMW28 in RA. The peak population of thrips was observed at RA during 30th SMW as (4.9 & 8.9 individuals per plant), respectively at Bt and non-Bt genotypes, declined to the lowest level of (0.1 & 0.3 individuals) in 41st SMW for both genotypes. Bt-cotton harbored relatively lower population of B. tabaci and T. tabaci in both fields owning to the presence of physico-morphich plant characters. A negative correlation of B. tabaci population was found with a maximum temperature and rainfall, and a positive relation with humidity. T. tabaci had a positive correlation with temperature and rainfall, and a negative correlation with relative humidity. The current research concluded that weather factors play and important role to increase or decrease the populations of sucking insect pests of cotton.